2019
DOI: 10.1017/s0024282919000380
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and assessment of the conservation status ofErioderma pedicellatumin Asia

Abstract: The first detailed survey is presented of a recently discovered population of Erioderma pedicellatum, a globally rare lichen, in the primeval spruce forests of the Kamchatka Peninsula, Russia. Three subpopulations are described, located in the Levaya Schapina River basin, in the Kimitina River basin, and on the slopes of the extinct volcano, Nikolka. In total, we observed 1894 thalli on 167 Yezo spruce trunks. In Kamchatka, E. pedicellatum occurs exclusively on bark-covered spruce twigs of mainly young and dwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…2013; Holien 2015; Tagirdzhanova et al . 2019). The lower part of the canyon represents a unique environment with epiphytes and microclimate resembling those in open patches of the Norwegian boreal rainforest (Holien & Tønsberg 1996), differing from the surrounding dry low-productive pine forest.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…2013; Holien 2015; Tagirdzhanova et al . 2019). The lower part of the canyon represents a unique environment with epiphytes and microclimate resembling those in open patches of the Norwegian boreal rainforest (Holien & Tønsberg 1996), differing from the surrounding dry low-productive pine forest.…”
Section: Methodsmentioning
confidence: 99%
“…2013 b ; Tagirdzhanova et al . 2019) and air pollution (Richardson & Cameron 2004), but wildfire (Tagirdzhanova et al . 2019) and gastropod grazing (Cameron 2009) are important local threats.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study successfully aged host trees and found that the number of thalli per tree peaked on 80-year-old trees (Tagirdzhanova et al . 2019), which is beyond the maximum average age of balsam fir in our study region. The patterns between boreal felt lichen host tree age, size and condition in these wetter areas is not well known.…”
Section: Discussionmentioning
confidence: 68%